Biomechanical analysis of transverse acetabular fracture fixation in the elderly via the posterior versus the anterior approach with and without a total hip arthroplasty. (September 2020) - Moktar, Joel; Machin, Alan; Bougherara, Habiba; Schemitsch, Emil H; Zdero, Radovan
This study provides the first biomechanical comparison of the fixation constructs that can be created to treat transverse acetabular fractures when using the "gold-standard" posterior versus the anterior approach with and without a total hip arthroplasty in the elderly. Synthetic hemipelvises partially simulating osteoporosis (n = 24) were osteotomized to create a transverse acetabular fracture and then repaired using plates/screws, lag screws, and total hip arthroplasty acetabular components in one of four ways: posterior approach (n = 6), posterior approach plus a total hip arthroplasty acetabular component (n = 6), anterior approach (n = 6), and anterior approach plus a total hip arthroplasty acetabular component (n = 6). All specimens were biomechanically tested. No differences existed between groups for stiffness (range, 324.6–387.3 N/mm, p = 0.629), clinical failure load at 5 mm of femoral head displacement (range, 1630.1–2203.9 N, p = 0.072), or interfragmentary gapping (range, 0.67–1.33 mm, p = 0.359). Adding a total hip arthroplasty acetabular component increased ultimate mechanical failure load for posterior (2904.4 vs. 3652.3 N, p = 0.005) and anterior (3204.9 vs. 4396.0 N, p = 0.000) approaches. Adding a total hip arthroplasty acetabular component also substantially reduced interfragmentary sliding for posterior (3.08 vs. 0.50 mm, p = 0.002) and anterior (2.17 vs. 0.29 mm, p = 0.024) approaches. Consequently, the anterior approach with a total hip arthroplasty may provide the best biomechanical stability for elderly patients, since this fixation group had the highest mechanical failure load and least interfragmentary sliding, while providing equivalent stiffness, clinical failure load, and gapping compared to other surgical options.